Employee Competence and the Effectiveness of the Integrated Internal Control System (SPIT): Mediating Effects of Leadership Commitment and the Moderating Role of Risk Management Maturity - Suryani Putri Albinar; Luke Suciati Amna (Indonesian Journal Publisher, 2025)
This study aims to analyze the effect of employee competence on the effectiveness of the Integrated Internal Control System (SPIT) at the Regional Office of the Directorate General of Treasury of Lampung Province, with leadership commitment as a mediating variable and risk management maturity as a moderating variable. The research employed a quantitative explanatory approach using a survey method. Primary data were collected through questionnaires distributed to 36 employees who had participated in SPIT socialization activities, and the sampling technique used was saturated sampling. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS version 3.8. The results show that employee competence has a positive and significant effect on SPIT effectiveness. Employee competence also has a positive and significant effect on leadership commitment, while leadership commitment positively and significantly influences SPIT effectiveness. Furthermore, leadership commitment partially mediates the relationship between employee competence and SPIT effectiveness. The findings also indicate that risk management maturity moderates the relationship between employee competence and SPIT effectiveness, strengthening the influence of employee competence on internal control effectiveness. These results highlight the importance of improving employee competence, strengthening leadership commitment, and enhancing risk management maturity to achieve effective implementation of SPIT in public sector organizations.